Multiple organ failure in the newborn: the point of view of the pathologist - Clara Gerosa; Eleonora Obinu; Daniela Fanni; Rossano Ambu; Gavino Faa (Hygeia Press di Corridori Marinella, 2014)
One of the most severe events occurring in critically ill patients admitted to a neonatal intensive care unit (NICU) center is represented by the multiple organ failure (MOF), a systemic inflammatory response leading to a progressive organ dysfunction and mortality in newborns. MOF may occur in newborns primarily affected by multiple single organ diseases, including respiratory distress syndrome neonatal sepsis with acute kidney injury, post-asphyxial hypoxic-ischemic encephalopathy and pandemic influenza A (H1N1) infection. In a previous article from our group, based on the histological examination of all organs at autopsy of newborns affected by MOF, all organs studied did not escape to be damaged, including thymus and pancreas normally not mentioned in the literature of MOF. The aim of this article is to review the most important pathological changes pathologists should look for in every case of MOF occurring in the perinatal period, with particular attention to systemic endothelial changes occurring in blood vessels in all organs and sytems. On the basis of our experience, matching data during the last phases of the clinicopathological diagnosis represents a useful method, much more productive as compared to the method based on giving pathological answers to the clinical questions prospected before autopsy. As for the pathological features observed in neonatal MOF, one of them deserves a particular attention: the vascular lesions, and in particular the multiple changes occurring during MOF development in endothelial cells, ending with the loss of the endothelial barrier, probably the most relevant histological lesion followed by the insurgence of interstitial edema and disseminated intravascular coagulation. Small vessels should be observed at high power, with particular attention to the size and shape of endothelial nuclei, in order to evidence endothelial swelling, probably the initial modification of the endothelial cells leading to their death. Finally, only the clinical pathological discussion may lead to a good diagnosis, correlating the morphological evidences with the clinical history and the sequence of clinical events that, at the best of our experience, are always different in a new case of MOF.   Proceedings of the International Course on Perinatal Pathology (part of the 10th International Workshop on Neonatology · October 22nd-25th, 2014) · Cagliari (Italy) · October 25th, 2014 · The role of the clinical pathological dialogue in problem solving Guest Editors: Gavino Faa, Vassilios Fanos, Peter Van Eyken